Ethnic Minority Women in the Scottish Labour Market: Employers' Perceptions. (6th March 2012) - Kamenou, Nicolina; Netto, Gina; Fearfull, Anne
Abstract : This paper contributes to an under‐researched area through investigating employers' perceptions of ethnic minority women in the Scottish labour market. Adopting a social constructionist approach which acknowledges agency and structure and incorporates insights relating to organizational and social group culture, the study highlights the influence of individual (micro), organizational (meso) and contextual (macro) factors on ethnic minority women's participation in the labour market. The paper is based on qualitative research involving Scottish employers in the public and private sectors to examine perceptions and practices related to the employment of ethnic minority women. Institutional commitment to equality issues is questioned, although individual instances of engagement with key equality issues were sometimes evident. Proactive recruitment strategies and career support for ethnic minority women and men were not in evidence, and there was low awareness of the unique position of ethnic minority women in employment and society. We argue that these findings call for a multi‐level approach to advancing human resources management policy, practice and research within a wider socio‐political environment in which the responsibilities and duties of public sector organizations are clarified and more support is provided for organizational promotion of equal opportunities.